A sigmoidal model for biosorption of heavy metal cations from aqueous media - SAYAR, AHMET ALP; SAYAR, NİHAT ALPAGU; DURMAZ ŞAM, SELÇEN (ELSEVIER SCIENCE INC, 2015)
A novel multi-input single output (MISO) black-box sigmoid model is developed to simulate the biosorption of heavy metal cations by the fission yeast from aqueous medium. Validation and verification of the model is done through statistical chi-squared hypothesis tests and the model is evaluated by uncertainty and sensitivity analyses. The simulated results are in agreement with the data of the studied system in which Schizosaccharomyces pombe biosorbs Ni(II) cations at various process conditions. Experimental data is obtained originally for this work using dead cells of an adapted variant of S. Pombe and represented by Freundlich isotherms. A process optimization scheme is proposed using the present model to build a novel application of a cost-merit objective function which would be useful to predict optimal operation conditions. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Modeling; Biosorption; Ni(II); Fission yeast; Validation; Optimization; NATURAL ORGANIC-MATTER; ION-BINDING; KINETICS; OPTIMIZATION; EXTRACTION; SIMULATION; NI(II)